Zinc halide phthalocyanine pigment and method for manufacturing the same

KR103012743B1Active Publication Date: 2026-09-01DIC CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
KR1020227045144
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-07-01
Filing Date
2021-06-03
Publication Date
2026-09-01
Estimated Expiration
2041-06-03

Smart Images

  • Figure R1020227045144_ABST
    Figure R1020227045144_ABST
Patent Text Reader

Abstract

The present invention provides a zinc halide phthalocyanine pigment that is used as a green pigment for color filters and can exhibit excellent brightness, and a method for manufacturing the same. A zinc halogenated phthalocyanine pigment comprising 1.00 parts by mass of the pigment, 0.95 parts by mass of a benzyl methacrylate-methacrylic acid copolymer, and 0.30 parts by mass of a dimethylaminoethyl methacrylate copolymer, heated at 230°C for 1 hour to form an evaluation film with a thickness of 4 μm, and from the two-dimensional scattering image obtained by GI-WAXS measurement of the evaluation film, an average scattering intensity in the range where the scattering angle 2θ is 17° to 21° is calculated, and when a normalized average scattering intensity with the average scattering intensity at an azimuth angle of 45° set to 1 is calculated, the normalized average scattering intensity at an azimuth angle of 5° to 89° is 0.70 to 1.15.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a zinc halide phthalocyanine pigment and a method for manufacturing the same. Background Technology

[0002] Currently, coloring compositions are used in various fields, and specific applications of coloring compositions include printing inks, paints, coloring agents for resins, coloring agents for textiles, and color materials for IT information recording (color filters, toners, inkjet). Colorants used in coloring compositions are broadly divided into pigments and dyes, and organic pigments are attracting attention as they are considered to be superior in terms of coloring power.

[0003] After synthesis, the organic compounds constituting organic pigments aggregate into fine particles and exist in the form of aggregates called crudes. Consequently, it is typically impossible to use the organic compounds directly as pigments after synthesis, so a pigmentization process is performed to adjust the particle size. The aggregates (crudes) of the organic compounds converted into pigments through this process are called crude pigments, and fine organic pigments can be obtained by grinding these crude pigments through methods such as kneading.

[0004] As an organic pigment, zinc halide phthalocyanine pigment, which is used in the green pixel portion of a color filter, is attracting attention (see, for example, Patent Document 1). Prior art literature

[0005] International Release Pamphlet No. 2018 / 043548 The problem to be solved

[0006] The present invention aims to provide a zinc halogenated phthalocyanine pigment that is used as a green pigment for color filters and can exhibit excellent brightness, and a method for manufacturing the same. means of solving the problem

[0007] It has been thought that using pigments with small primary particle sizes (fine pigments) is particularly effective for improving the luminance, which is a characteristic value of color filters. Therefore, the development of pigments that enable further high luminance of color filters has been carried out from the perspective of how much finer the crude pigment is processed into the pigment during the pigmentation process.

[0008] However, since there are limitations to the micronization of pigments, the inventors investigated methods to achieve high brightness other than micronization. During this investigation, the inventors discovered, through a detailed analysis of zinc halogenated phthalocyanine (crude pigment) prior to pigmentation, that color filters using the crude pigment exhibited strong orientation in a direction horizontal to the film. Therefore, the inventors conceived of a method to perform pigmentation that could mitigate the aforementioned orientation compared to conventional pigmentation methods using a kneader or similar equipment, and after further investigation, completed the present invention.

[0009] One aspect of the present invention relates to a zinc halogenated phthalocyanine pigment. A coating film comprising 1.00 parts by mass of the zinc halogenated phthalocyanine pigment, 0.95 parts by mass of a benzyl methacrylate-methacrylic acid copolymer, and 0.30 parts by mass of a dimethylaminoethyl methacrylate copolymer is heated at 230°C for 1 hour to form an evaluation coating film with a thickness of 4 μm, and from the two-dimensional scattering image obtained by GI-WAXS measurement of the evaluation coating film, the average scattering intensity in the range where the scattering angle 2θ is 17° to 21° is calculated, and when the normalized average scattering intensity with the average scattering intensity at an azimuth angle of 45° being 1 is calculated, the normalized average scattering intensity at an azimuth angle of 5° to 89° is 0.70 to 1.15.

[0010] According to the zinc halogenated phthalocyanine pigment of the above aspect, the brightness of the green color filter can be improved.

[0011] In one embodiment, the average primary particle size of the pigment is preferably 30 nm or less. Effects of the invention

[0012] According to the present invention, a zinc halide phthalocyanine pigment that is used as a green pigment for color filters and can exhibit excellent brightness, and a method for manufacturing the same can be provided. Brief explanation of the drawing

[0013] FIG. 1 is a diagram showing the two-dimensional scattering images of the reference example, comparative example, and example. FIG. 2 is a diagram showing the azimuth profiles of the reference example, comparative example, and example at azimuths of 5° to 89°. FIG. 3 is a figure showing the azimuth profiles of the reference example, comparative example, and example at an azimuth of 45° to 55°. Specific details for implementing the invention

[0014] Suitable embodiments of the present invention are described below. However, the present invention is not limited in the slightest to the following embodiments.

[0015] <Zinc Halide Phthalocyanine Pigment>

[0016] A zinc phthalocyanine halogenated pigment of one embodiment is composed of one or more particles containing one or more types of zinc phthalocyanines with different numbers of halogen atoms. Here, the zinc phthalocyanine halogenated is a compound having a structure represented by the following formula (1).

[0017]

[0018] [In Equation (1), X 1 ~X 16 Each represents, independently, a hydrogen atom or a halogen atom.

[0019] Examples of halogen atoms include fluorine atoms, chlorine atoms, bromine atoms, and iodine atoms. It is preferable for zinc halogenated phthalocyanine to have at least one of a bromine atom and a chlorine atom as halogen atoms, and it is preferable for it to have a bromine atom. Zinc halogenated phthalocyanine may have only one or both of a chlorine atom and a bromine atom as halogen atoms. That is, X in the above formula (1). 1 ~X 16 It may be silver, chlorine atoms, or bromine atoms.

[0020] In one embodiment, the average number of bromine atoms in one molecule of the compound represented by Formula (1) in the zinc halide phthalocyanine pigment is less than 13. The average number of bromine atoms may be 12 or fewer, or 11 or fewer. The average number of bromine atoms may be 0.1 or more, 6 or more, or 8 or more. The upper and lower limits described above may be combined arbitrarily. For example, the average number of bromine atoms may be 0.1 or more and less than 13, 8 to 12, or 8 to 11. Furthermore, in the same description below, the upper and lower limits described individually may be combined arbitrarily.

[0021] When the average number of bromine atoms is less than 13, the average number of halogen atoms in one molecule of the compound represented by formula (1) in the zinc halogenated phthalocyanine pigment may be 14 or fewer, 13 or fewer, less than 13, or 12 or fewer. The average number of halogen atoms may be 0.1 or more, or 8 or more, or 10 or more.

[0022] When the average number of bromine atoms is less than 13, the average number of chlorine atoms in one molecule of the compound represented by formula (1) in the zinc halide phthalocyanine pigment may be 5 or fewer, 3 or fewer, 2.5 or fewer, or less than 2. The average number of chlorine atoms may be 0.1 or more, 0.3 or more, 0.6 or more, 0.8 or more, 1 or more, 1.3 or more, or 2 or more.

[0023] In another embodiment, the average number of bromine atoms in one molecule of the compound represented by formula (1) in the zinc halide phthalocyanine pigment is 13 or more. The average number of bromine atoms may be 14 or more. The average number of bromine atoms may be 15 or less.

[0024] When the average number of bromine atoms is 13 or more, the average number of halogen atoms in one molecule of the compound represented by Formula (1) in the zinc halogenated phthalocyanine pigment may be 13 or more, 14 or more, or 15 or more. The average number of halogen atoms may be 16 or less, or 15 or less.

[0025] When the average number of bromine atoms is 13 or more, the average number of chlorine atoms in one molecule of the compound represented by Formula (1) in the zinc halide phthalocyanine pigment may be 0.1 or more or 1 or more. The average number of chlorine atoms may be 3 or fewer or less than 2.

[0026] The number of the above halogen atoms (e.g., the number of bromine atoms and chlorine atoms) can be determined by mass analysis of the zinc halogenated phthalocyanine pigment using, for example, a matrix-assisted laser-derived ionization time-of-flight mass spectrometer (e.g., JMS-S3000 manufactured by Nippon Electronics Co., Ltd.). Specifically, the number of each halogen atom can be calculated as a relative value per zinc atom from the mass ratio of zinc atoms to each halogen atom in the zinc halogenated phthalocyanine pigment.

[0027] In one embodiment, the zinc halogenated phthalocyanine pigment has an orientation parameter (A) of 0.70 to 1.15. Here, the orientation parameter (A) is a parameter derived by GI-WAXS (Grazing-Incidence Wide-Angle X-ray Scattering) measurement of an evaluation film with a thickness of 4 μm formed using 1.00 parts by mass of zinc halogenated phthalocyanine pigment and 1.25 parts by mass of resin.

[0028] GI-WAXS measurement is a method of measuring X-ray scattering generated by incident X-rays being incident on a sample surface (the surface of an evaluation film) at a minute angle of approximately 0.1°. In GI-WAXS measurement, structural information of a sample can be obtained by irradiating the sample surface with X-rays and measuring the X-rays with large scattering angles among the scattered X-rays. Specifically, by exposing the scattered X-ray light from the sample to a two-dimensional detector, a circular profile of scattering intensity centered on the center of the X-ray beam (azimuthal intensity distribution) can be obtained as a two-dimensional X-ray scattering image (scattering profile), and structural information of the sample can be obtained by analyzing the obtained two-dimensional X-ray scattering image. In addition to being used for crystal structure analysis, GI-WAXS measurement is also used to acquire information on the orientation of a sample.

[0029] Generally, when a sample has a random orientation, X-ray scattering from the sample exhibits uniform circular scattering on the plane of a two-dimensional detector. In contrast, it is known that when a sample has a horizontal orientation, X-ray scattering is stronger in the vertical direction on the plane of the two-dimensional detector, and when a sample has a vertical orientation, it is stronger in the horizontal direction on the plane of the two-dimensional detector. Therefore, the orientation of the sample can be investigated by analyzing the two-dimensional X-ray scattering image (a circular profile of scattering intensity centered on the center of the X-ray beam) obtained from the two-dimensional detector. The orientation parameter (A) is a quantitative representation of the intensity of the orientation of the sample analyzed by this method.

[0030] The orientation parameter (A) is specifically obtained as follows. First, from the two-dimensional scattering image obtained by GI-WAXS measurement, the average scattering intensity is obtained in the range where the scattering angle 2θ is 17° to 21° within the range of azimuth angles 5° to 89°. Here, the azimuth angle is an angle in which the horizontal plane of the detector is set to 0°. Next, each average scattering intensity in the range of azimuth angles 5° to 89° is normalized by dividing it by the average scattering intensity in the range of azimuth angle 45° so that the value of the azimuth angle 45° becomes 1. The normalized average scattering intensity (normalized average scattering intensity) in the range of azimuth angles 5° to 89° obtained in this way is used as the orientation parameter (A).

[0031] Since the normalized average scattering intensity represents the intensity of orientation, an orientation parameter (A) of 0.70 to 1.15 means that the intensity of orientation (minimum and maximum values ​​of normalized average scattering intensity at azimuths of 5° to 89°) falls within a certain range.

[0032] The evaluation film used for GI-WAXS measurement can be obtained specifically by forming a film of an evaluation composition comprising 1.00 parts by mass of zinc halide phthalocyanine pigment, 1.25 parts by mass of resin, and an organic solvent on a glass substrate, drying the obtained film to remove the organic solvent, and further heating at 230°C for 1 hour. Here, the resin comprises 0.95 parts by mass of a copolymer of benzyl methacrylate and methacrylic acid (benzyl methacrylate-methacrylic acid copolymer) and 0.30 parts by mass of a copolymer containing dimethylaminoethyl methacrylate in the polymerization unit (dimethylaminoethyl methacrylate copolymer).

[0033] The benzyl methacrylate-methacrylic acid copolymer is provided, for example, as Unidic ZL-295 manufactured by DIC Corporation (a solution with a solid content of 40 mass%). The weight average molecular weight (Mw) of the benzyl methacrylate-methacrylic acid copolymer is, for example, 12,000 to 16,000.

[0034] The dimethylaminoethyl methacrylate copolymer is provided, for example, as BYK-LPN6919 manufactured by Big Chem (a solution with a solid content of 60 mass%). The weight average molecular weight (Mw) of the dimethylaminoethyl methacrylate copolymer is, for example, 7000 to 11000.

[0035] The dimethylaminoethyl methacrylate copolymer is a copolymer that forms a pigment dispersion having a viscosity of 10 mPa·s or less at 25°C when, for example, 30 g of Pigment Green 58 (e.g., FASTOGEN Green A110 manufactured by DIC Corporation), 22.5 g of a resin solution with a solid content of 40 mass% of the above benzyl methacrylate-methacrylic acid copolymer (e.g., ZL-295 manufactured by DIC Corporation), 132.5 g of propylene glycol monomethyl ether acetate, and 15 g of a resin solution with a solid content of 60 mass% of the dimethylaminoethyl methacrylate copolymer are dispersed for 2 hours in a paint shaker using 460 g of zircon beads of 0.3 to 0.4 mm. In addition, the above viscosity is the viscosity measured by a cone-plate type rotary clay system (cone plate clay system) (e.g., RE550L of Toki Industry Co., Ltd.) in accordance with JIS Z8803.

[0036] As an organic solvent, an organic solvent capable of dissolving the resin without dissolving zinc halogenated phthalocyanine is preferred, and specifically, propylene glycol monomethyl ether acetate is preferred.

[0037] A composition for evaluation comprises, for example, 0.992 parts by mass of a zinc halide phthalocyanine pigment, 0.744 parts by mass of a resin solution of a benzyl methacrylate-methacrylic acid copolymer with a solid content of 40% by mass, 0.496 parts by mass of a resin solution of a dimethylaminoethyl methacrylate copolymer with a solid content of 60% by mass, and 4.368 parts by mass of an organic solvent, combined with 15.2 parts by mass of zircon beads of 0.3 to 0.4 mm, dispersed in a paint shaker (e.g., a paint shaker manufactured by Toyo Seiki Co., Ltd.) for 2 hours to obtain a pigment dispersion, and then 3.000 parts by mass of the obtained pigment dispersion, 0.735 parts by mass of a resin solution of a benzyl methacrylate-methacrylic acid copolymer with a solid content of 40% by mass, and 0.165 parts by mass of an organic solvent, and a paint shaker (e.g. It may be prepared by mixing using a paint shaker manufactured by Toyo Seiki Co., Ltd.

[0038] The formation of a film of the evaluation composition can be performed, for example, by spin coating. The spin coating conditions (rotation speed and amount of evaluation composition) should be adjusted so that the thickness of the final film obtained is 4 μm. As a glass substrate used for forming the film of the evaluation composition, so-called white glass made using a highly transparent material such as borosilicate glass is preferred. As such a glass substrate, Corning (registered trademark) EAGLE XG, etc., can be used.

[0039] The drying conditions are, for example, 70 to 100 minutes at 70 to 100°C.

[0040] GI-WAXS measurement can be performed by placing a sample substrate having a sample (evaluation film) that is smoothly fabricated on a substrate such that the distance from the center of the sample (the center of the surface of the evaluation film) to the detector is 102.5 mm, and placing the sample substrate on the sample stage of a GI-WAXS measurement device (grazing incident X-ray scattering device), and setting the X-ray wavelength to 0.1 nm and the X-ray incidence angle to 0.06°.

[0041] In order to accurately obtain the scattering profile of the evaluation film by GI-WAXS measurement, more (specifically 10 16 (photons / sec / mm 2 / mrad 2 It is necessary to measure X-ray scattering of 0.1% bandwidth or higher. For this reason, for GI-WAXS measurements, it is desirable to use a high-intensity X-ray source capable of measuring more scattering in a short time. To obtain a high-intensity X-ray source, light sources from large synchrotron facilities, such as SPring-8 in Hyogo Prefecture or PhotonFactory in Ibaraki Prefecture, can be used.

[0042] In a GI-WAXS measurement device at a synchrotron radiation facility, white light extracted from a circular accelerator called an accumulation ring is monochromated by a two-crystal spectrometer, and X-rays are incident on the center of a sample (the center of the surface of the evaluation film) of a sample substrate installed on a sample stage using a wavelength in the X-ray region (e.g., 1 Å) as a source, and the scattered light is exposed to a two-dimensional detector. By doing so, a two-dimensional X-ray scattering image can be obtained.

[0043] When a zinc halogenated phthalocyanine pigment having an orientation parameter (A) in the above range is used as a green pigment for a color filter, it contributes to the expression of excellent brightness. The reason for this effect is presumed to be that when a zinc halogenated phthalocyanine pigment is oriented within a color filter, it scatters the white light (white transmitted light) passing through the color filter, resulting in a decrease in brightness and contrast, whereas a zinc halogenated phthalocyanine pigment having an orientation parameter (A) of 0.70 to 1.15 is difficult to align within a color filter, and thus, by using the zinc halogenated phthalocyanine pigment, the scattering of white transmitted light is suppressed. When a zinc halogenated phthalocyanine pigment having an orientation parameter (A) in the above range is used as a green pigment for a color filter, excellent contrast also tends to be obtained, and this is also presumed to be due to the same reason as above.

[0044] The orientation parameter (A) is preferably 0.73 to 1.14 and more preferably 0.75 to 1.13 in terms of being easier to obtain better luminance and contrast.

[0045] In another embodiment, the zinc halogenated phthalocyanine pigment has an orientation parameter (C) of -0.006 to 0.006. Here, the orientation parameter (C) is a parameter derived by GI-WAXS measurement of an evaluation film with a thickness of 4 μm formed using 1 part by mass of zinc halogenated phthalocyanine pigment and 1.25 parts by mass of resin, just like the orientation parameter (A) described above. The evaluation composition used for measurement, the method of forming the evaluation film, and the GI-WAXS measurement method are the same as those for the orientation parameter (A).

[0046] Specifically, the orientation parameter (C) is obtained as follows. First, from the two-dimensional scattering image obtained by GI-WAXS measurement, the average scattering intensity is obtained in the range of scattering angle 2θ from 17° to 21° within the range of azimuth angle 45° to 55°. Next, each average scattering intensity in the range of azimuth angle 45° to 55° is normalized by dividing it by the average scattering intensity in the range of azimuth angle 45° so that the value of azimuth angle 45° becomes 1. Next, in the range of azimuth angle 45° to 55°, an azimuth profile (a graph with the horizontal axis as the azimuth angle) is created with the normalized average scattering intensity (normalized average scattering intensity) obtained above as the vertical axis, and a linear approximation is performed, and the slope of the obtained approximation line is used as the orientation parameter (C).

[0047] As revealed by the inventors' examination, zinc halide phthalocyanine pigments tend to exhibit a strong orientation at an azimuth angle of 45° to 55°. Therefore, the small slope of the above approximate straight line means that a significant increase in orientation intensity, which is prone to occur particularly in zinc halide phthalocyanine pigments, is suppressed.

[0048] When zinc halogenated phthalocyanine pigments having an orientation parameter (C) in the above range are used as green pigments for color filters, they contribute to the expression of excellent brightness. Although the reason for this effect is not clear, it is presumed that because zinc halogenated phthalocyanine pigments having an orientation parameter (C) of -0.006 to 0.006 are difficult to align within the color filter, scattering of white transmitted light is suppressed by using said zinc halogenated phthalocyanine pigments. When zinc halogenated phthalocyanine pigments having an orientation parameter (C) in the above range are used as green pigments for color filters, excellent contrast also tends to be obtained, which is also presumed to be due to the same reason as above.

[0049] The orientation parameter (C) is preferably -0.0055 to 0.0055 and more preferably -0.0050 to 0.0050, in terms of making it easier to obtain better luminance and contrast. It is believed that the same effect can be obtained whether the value of the orientation parameter (C) is positive or negative as long as it is small in absolute value. However, as a result of the inventors' investigation, it was found that there is a tendency for positive values ​​to appear in zinc halide phthalocyanine pigments. Therefore, the orientation parameter (C) is more preferably 0 to 0.0055 and particularly preferably 0.001 to 0.0050.

[0050] The average primary particle size of the zinc halide phthalocyanine pigment is preferably 30 nm or less, and more preferably 25 nm or less, from the perspective of making it easier to obtain better luminance and contrast. The average primary particle size of the zinc halide phthalocyanine pigment should be 10 nm or more. Here, the average primary particle size is the average value of the major axis of the primary particles, and can be obtained by measuring the major axis of the primary particles in the same way as the measurement of the average aspect ratio described later.

[0051] The average aspect ratio of the primary particles of the zinc halide phthalocyanine pigment is, for example, 1.2 or more, 1.3 or more, 1.4 or more, or 1.5 or more. The average aspect ratio of the primary particles of the zinc halide phthalocyanine pigment is, for example, less than 2.0, 1.8 or less, 1.6 or less, or 1.4 or less. With the zinc halide phthalocyanine pigment having such an average aspect ratio, better contrast can be obtained.

[0052] A zinc halide phthalocyanine pigment having an average aspect ratio of primary particles in the range of 1.0 to 3.0 is preferably not to contain primary particles with an aspect ratio of 5 or more, more preferably not to contain primary particles with an aspect ratio of 4 or more, and more preferably not to contain primary particles with an aspect ratio exceeding 3.

[0053] The aspect ratio and average aspect ratio of primary particles can be measured by the following method. First, particles within the field of view are photographed using a transmission electron microscope (e.g., JEM-2010 manufactured by Nippon Electronics Co., Ltd.). Then, the long axis (major axis) and short axis (minor axis) of the primary particles present in the two-dimensional image are measured, and the ratio of the major axis to the minor axis is defined as the aspect ratio of the primary particles. Furthermore, the average values ​​of the major axis and minor axis are calculated for 40 primary particles, and the ratio of the major axis to the minor axis is calculated using these values ​​and defined as the average aspect ratio. At this time, the sample zinc halide phthalocyanine pigment is ultrasonically dispersed in a solvent (e.g., cyclohexane) and then photographed with a microscope. Additionally, a scanning electron microscope may be used instead of a transmission electron microscope.

[0054] The zinc halide phthalocyanine pigment described above is suitable for use as a green pigment for color filters because it can improve the brightness and contrast of green color filters.

[0055] <Method for Manufacturing Zinc Halide Phthalocyanine Pigment>

[0056] A method for manufacturing a zinc halogenated phthalocyanine pigment of one embodiment comprises a first step of preparing a zinc halogenated phthalocyanine crude pigment and a second step (pigmentation process) of making the zinc halogenated phthalocyanine crude pigment into a pigment.

[0057] In the first process, a zinc phthalocyanine halogenated pigment is prepared. The zinc phthalocyanine halogenated pigment is, for example, obtained by precipitating zinc phthalocyanine immediately after synthesis (for example, an aggregate of zinc phthalocyanine halogenated), and contains one type or multiple types of zinc phthalocyanine halogenated with different numbers of halogen atoms.

[0058] The first process includes a process of synthesizing zinc halogenated phthalocyanine by a known manufacturing method, such as, for example, the chlorosulfonic acid method, the phthalonitrile halogenated method, or the melting method, and a process of precipitating the synthesized zinc halogenated phthalocyanine to obtain a zinc halogenated phthalocyanine crude pigment. The process of synthesizing zinc halogenated phthalocyanine may, for example, be a process of synthesizing zinc halogenated phthalocyanine using a compound that reacts with water to generate acid. Examples of methods for synthesizing zinc halogenated phthalocyanine using a compound that reacts with water to generate acid include the chlorosulfonic acid method and the melting method.

[0059] As an example of the chlorosulfonic acid method, zinc phthalocyanine is dissolved in a sulfur oxide-based solvent such as chlorosulfonic acid, and then halogenated by adding chlorine gas and bromine. The reaction is carried out, for example, at a temperature of 20 to 120°C and for 3 to 20 hours. In the chlorosulfonic acid method, the sulfur oxide-based solvent, such as the chlorosulfonic acid mentioned above, is a compound that reacts with water to produce an acid. For example, chlorosulfonic acid reacts with water to produce hydrochloric acid and sulfuric acid.

[0060] As a phthalonitrile halogenation method, for example, a method for synthesizing the corresponding zinc phthalocyanine halogenation can be described by using phthalic acid or phthalodinitrile, in which some or all of the hydrogen atoms of the aromatic ring are substituted with halogen atoms such as chlorine in addition to bromine, and zinc metal or a metal salt as suitable starting materials. In this case, a catalyst such as ammonium molybdate may be used if necessary. The reaction at this time is carried out, for example, at a temperature of 100 to 300°C and for 7 to 35 hours.

[0061] As a melting method, a method of halogenating zinc phthalocyanine with a halogenating agent in a molten solution of about 10 to 170°C, which consists of one or more of the compounds that serve as solvents during halogenation, such as aluminum halides (aluminum chloride, aluminum bromide, etc.), titanium halides (titanium tetrachloride, etc.), alkali metal halides (alkali (earth) metal halides) or alkaline earth metal halides (alkali (earth) metal halides) (hereinafter referred to as "alkali (earth) metal halides"), and thionyl chloride, etc. In the melting method, the compounds that serve as solvents during halogenation, such as the aluminum halides, titanium halides, alkali (earth) metal halides, and thionyl chloride, are compounds that react with water to produce acid. For example, aluminum chloride reacts with water to produce hydrochloric acid.

[0062] Suitable aluminum halide is aluminum chloride. In the above method using aluminum halide, the amount of aluminum halide added is usually 3 times the moles of zinc phthalocyanine, and preferably 10 to 20 times the moles.

[0063] Aluminum halides may be used alone, but using alkali (earth) metal halides in combination with aluminum halides allows the melting temperature to be lowered further, which is advantageous for operation. A suitable alkali (earth) metal halide is sodium chloride. Within the range for producing molten salt, the amount of alkali (earth) metal halide added is preferably 1 to 15 parts by mass of alkali (earth) metal halide per 10 parts by mass of aluminum halides.

[0064] Examples of halogenating agents include chlorine gas, sulferyl chloride, and bromine.

[0065] The temperature of the halogenation is preferably 10 to 170°C, and more preferably 30 to 140°C. In addition, it is possible to apply pressure to accelerate the reaction rate. The reaction time may be 5 to 100 hours, and preferably 30 to 45 hours.

[0066] A melting method using two or more of the above compounds is desirable because it allows for arbitrary control of the content ratio of zinc phthalocyanine with a specific halogen atom composition in the zinc phthalocyanine produced by adjusting the ratio of chloride, bromide, and iodide in the molten salt, or by changing the amount of chlorine gas, bromine, iodine, etc. introduced and the reaction time. In addition, according to the melting method, the decomposition of raw materials during the reaction is minimal and the yield from the raw materials is superior, so the reaction can be carried out with low-cost equipment without using strong acids.

[0067] In this embodiment, by optimizing the method of adding raw materials, the catalyst species and the amount used, the reaction temperature, and the reaction time, zinc phthalocyanine with a halogen atom composition different from conventional zinc phthalocyanine can be obtained. More specifically, zinc phthalocyanine with a halogen atom composition that can be included in the zinc phthalocyanine pigment described above can be obtained.

[0068] In any of the above methods, after the reaction is completed, the obtained mixture is introduced into an acidic aqueous solution such as water or hydrochloric acid, or a basic aqueous solution such as sodium hydroxide, and the resulting zinc halide phthalocyanine is precipitated. At this time, if a compound that reacts with water to generate acid is used, acids such as hydrochloric acid or sulfuric acid are generated, but if a basic aqueous solution is used, the generation of acid is suppressed. By doing so, the inclusion of acid in the precipitate can be suppressed, thereby preventing acid from remaining in the crude pigment. It is believed that if the crude pigment contains acid, particle aggregation caused by the acid is promoted during pigment formation, thereby hindering the refinement of pigment particles; however, by reducing the acid contained in the crude pigment using the above method, finer pigment particles can be obtained.

[0069] The first process may additionally include a post-treatment process for post-treating the precipitate after the precipitation process.

[0070] The first process may additionally include, for example, a process for filtering the precipitate (a first post-treatment process). The first post-treatment process may be a process for filtering and washing the precipitate, or a process for filtering, washing, and drying the precipitate. Washing may be performed using an aqueous solvent, for example, water, sodium bisulfate solution, sodium bicarbonate solution, sodium hydroxide solution, etc. In washing, organic solvents such as acetone, toluene, methyl alcohol, ethyl alcohol, dimethylformamide, etc. may be used as needed. For example, washing with an organic solvent may be performed after washing with an aqueous solvent. Washing may be repeated multiple times (for example, 2 to 5 times). Specifically, it is preferable to perform washing until the pH of the filtrate becomes equal to the pH of the water used for washing (for example, the difference between the two is 0.2 or less).

[0071] The first process may additionally include, for example, a process of dry grinding the precipitate (second post-treatment process). Dry grinding may be performed, for example, in a grinder such as an attritor, a ball mill, a vibrating mill, or a vibrating ball mill. Dry grinding may be performed while heating (for example, while heating the temperature inside the grinder to 40°C to 200°C). Washing with water may be performed after dry grinding. By washing with water after dry grinding (especially after dry grinding by an attritor), the amount of acid contained in the crude pigment can be further reduced. Washing may be either water washing (washing with water below 40°C) or hot water washing (washing with water above 40°C). Washing is preferably performed until the pH of the filtrate becomes equal to the pH of the water used for washing (for example, the difference between the two is 0.2 or less), just as in the first post-treatment process. In addition, during or prior to washing with water, a treatment to improve the wettability of the precipitate (e.g., a treatment of contacting the precipitate with a water-soluble organic solvent such as methanol) may be performed. Dry grinding and washing may be repeated multiple times.

[0072] The first process may additionally include, for example, a process of kneading the precipitate with water (third post-treatment process). By performing the third post-treatment process, the amount of acid contained in the crude pigment can be further reduced. Kneading may be performed using, for example, a kneader, a mixer, etc. Kneading may be performed while heating. For example, the temperature of the water may be 40°C or higher. Inorganic salts may be added to the water. At this time, by allowing at least some of the inorganic salts to exist in a solid form, the force applied during kneading can be enhanced. An organic solvent (for example, an organic solvent that can be used in the second process described later) may be used during kneading, but it is preferable that the amount of organic solvent used be less than the amount of water, and it is more preferable not to use an organic solvent. After kneading, washing may be performed in the same manner as the first post-treatment process. Kneading and washing may be repeated multiple times.

[0073] The first process may additionally include a process of heating the precipitate in water (e.g., boiling) (a fourth post-treatment process). By performing the fourth post-treatment process, the amount of acid contained in the crude pigment can be further reduced. The heating temperature in water may be, for example, 40°C or higher and below the boiling point, and the heating time may be, for example, 1 to 300 minutes. An organic solvent (e.g., an organic solvent that can be used in the second process described later) may be mixed in the water, and the amount of organic solvent mixed is preferably 20 parts by mass or less per 100 parts by mass of water. In the fourth post-treatment process, with the view of further removing acid, washing may be performed after heating the precipitate in water, or washing may be performed after heating the precipitate in water, and additionally, heating and washing in water may be repeated one or more times (preferably two or more times). Cleaning may be performed in the same manner as the first post-treatment process.

[0074] In this embodiment, two or more of the first to fourth post-processing processes described above may be performed. When two or more of the first to fourth post-processing processes are performed, the order thereof is not particularly limited.

[0075] A zinc halogenated phthalocyanine crude pigment is obtained by the first process above. As described above, in this embodiment, the precipitate obtained in the first process may be used as is for the zinc halogenated phthalocyanine crude pigment, or the precipitate subjected to the post-treatment process (at least one of the first to fourth post-treatment processes) may be used for the zinc halogenated phthalocyanine crude pigment. When water is used in the second process, drying is not required in the first process. That is, when water is used in the second process, the undried zinc halogenated phthalocyanine crude pigment (a mixture of zinc halogenated phthalocyanine crude pigment and water) obtained in the first process may be used in the second process.

[0076] The arithmetic standard deviation of the particle size distribution of the zinc halide phthalocyanine crude pigment is, for example, 15 nm or more. The arithmetic standard deviation of the particle size distribution of the zinc halide phthalocyanine crude pigment is, for example, 1500 nm or less. If the arithmetic standard deviation of the particle size distribution of the zinc halide phthalocyanine crude pigment is within this range, it becomes easier to obtain finer pigment particles. The arithmetic standard deviation of the particle size distribution of the zinc halide phthalocyanine crude pigment can be measured using a dynamic light scattering particle size distribution measuring device, and specifically, can be measured under the following methods and conditions.

[0077] (method)

[0078] 2.48 g of zinc halide phthalocyanine crude pigment is dispersed for 2 hours in a paint shaker manufactured by Toyo Seiki Co., Ltd. along with 1.24 g of BYK-LPN6919 manufactured by Big Chem Co., Ltd., 1.86 g of Unidic ZL-295 manufactured by DIC Co., Ltd., and 10.92 g of propylene glycol monomethyl ether acetate, using zircon beads of 0.3 to 0.4 mm. The resulting mixture is then diluted with 20 g of propylene glycol monomethyl ether acetate to obtain a dispersion for particle size distribution measurement.

[0079] (condition)

[0080] · Measuring instrument: Dynamic light scattering particle size distribution measuring device LB-550 (Manufactured by Horiba, Inc.)

[0081] · Measured temperature: 25℃

[0082] · Measurement sample: Dispersion for particle size distribution measurement

[0083] · Data interpretation conditions: Scattered light intensity based on particle size, dispersion medium refractive index 1.402

[0084] In the second process, the zinc halide phthalocyanine crude pigment obtained in the first process is converted into a pigment.

[0085] In one embodiment, the second process includes a process for grinding the zinc halogenated phthalocyanine pigment (hereinafter referred to as the “grinding process”) by applying pressure to a mixture (hereinafter referred to as “mixture (A”)) comprising the zinc halogenated phthalocyanine pigment and an organic solvent with a pair of opposing members (e.g., plate-shaped members) and rotating one or both of the pair of members.

[0086] According to the above grinding process, the zinc halide phthalocyanine crude pigment can be fined while simultaneously controlling its orientation. Specifically, the grinding process can be carried out using a Huber-Müller (also called an automatic Huber-Müller). In this case, a pair of opposing members are glass plates, and the zinc halide phthalocyanine crude pigment is ground by applying a load from one glass plate to compress the mixture (A) and rotating one glass plate in a direction perpendicular to the opposing direction.

[0087] The amount of mixture (A) used is such that the mixture (A) does not leak out between the pair of members that press the mixture (A) during grinding, and may be appropriately adjusted according to the size of the members.

[0088] The pressure (e.g., the magnitude of the load applied from the glass plate) is preferably 5 kPa (kilopascal) or more, more preferably 10 kPa or more, and even more preferably 20 kPa or more, in terms of increasing the shear stress applied to the mixture during grinding. The pressure is preferably 200 kPa or less, more preferably 100 kPa or less, and even more preferably 50 kPa or less, in terms of preventing the crushing of pigment particles.

[0089] The rotation conditions of the member are preferably 50 to 3000 times at 30 to 300 rpm, more preferably 60 to 1000 times at 50 to 200 rpm, and even more preferably 70 to 300 times at 70 to 150 rpm, in order to increase the shear stress applied to the mixture during grinding. In addition, when both sides of a pair of members are rotating, the rotation speed is the rotation speed of the other member assuming that one side of the pair of members is stationary.

[0090] In the grinding process, since the mixture (A) spreads on the surface of the member by the rotation of the member, the member may be rotated multiple times, the pressure may be released, the mixture (A) spread on the surface of the member may be gathered to the center of the member, and then grinding may be performed again by pressure and rotation. In this case, the above preferred number of rotations refers to the total number of rotations.

[0091] The temperature during grinding (e.g., the temperature of the surface in contact with the mixture of materials) is, for example, 0 to 100°C. In the grinding process, the halogenated phthalocyanine crude pigment may be ground while cooling or heating.

[0092] For the organic solvent, it is preferable to use one that does not dissolve the zinc halide phthalocyanine crude pigment and the inorganic salt described below. As for the organic solvent, it is preferable to use an organic solvent capable of inhibiting crystal growth. Water-soluble organic solvents can be appropriately used as such an organic solvent. As organic solvents, for example, diethylene glycol, glycerin, ethylene glycol, propylene glycol, 1,3-propanediol, 1,3-butanediol, liquid polyethylene glycol, liquid polypropylene glycol, 2-(methoxymethoxy)ethanol, 2-butoxyethanol, 2-(isopentyloxy)ethanol, 2-(hexyloxy)ethanol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, triethylene glycol, triethylene glycol monomethyl ether, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, trimethyl phosphate, 4-butyrolactone, propylene carbonate, N-methyl-2-pyrrolidone, methanol, ethylene cyanohydrin, 1,2,4-butanetriol, 1,2,5-pentanetriol, etc. may be used. Organic solvents may be used individually or in combination of multiple types.

[0093] As for the organic solvent, it is preferable to use a triol having 3 to 5 carbon atoms in order to have high viscosity and to make it easier to apply sufficient shear stress to the mixture (A), more preferable to use at least one selected from the group consisting of 1,2,4-butanetriol, glycerin, and 1,2,5-pentanetriol, and more preferable to use 1,2,4-butanetriol.

[0094] The amount of organic solvent (e.g., water-soluble organic solvent) used is not particularly limited, but is preferably 1 to 500 parts by weight per 100 parts by weight of zinc halide phthalocyanine crude pigment. The amount of organic solvent (e.g., water-soluble organic solvent) used per 100 parts by weight of zinc halide phthalocyanine crude pigment may be 30 parts by weight or more or 50 parts by weight or more, or 400 parts by weight or less or 200 parts by weight or less.

[0095] In the grinding process, the crude zinc halide phthalocyanine pigment may be ground by kneading it together with an inorganic salt. That is, in the grinding process, a mixture (A) containing the crude zinc halide phthalocyanine pigment, an organic solvent, and an inorganic salt may be used. By using an inorganic salt, the force applied to the crude zinc halide phthalocyanine pigment during the grinding process can be improved, thereby enabling the production of finer pigment particles.

[0096] As for the inorganic salt, an inorganic salt having solubility in water and / or methanol is preferably used. For example, inorganic salts such as sodium chloride, potassium chloride, lithium chloride, and sodium sulfate are preferably used. The average particle size of the inorganic salt is preferably 0.5 to 50 μm. Such an inorganic salt is easily obtained by finely grinding a conventional inorganic salt.

[0097] In the grinding process, it is preferable not to use water. That is, it is preferable that the mixture (A) used in the grinding process does not contain water. The amount of water used (water content in the mixture) may be, for example, 20 parts by mass or less, 10 parts by mass or less, or 5 parts by mass or less, per 100 parts by mass of zinc halide phthalocyanine crude pigment.

[0098] In the grinding process, when inorganic salts and organic solvents are used, a mixture containing zinc halide phthalocyanine pigment, inorganic salts, and organic solvents can be obtained. The organic solvents and inorganic salts can be removed from this mixture, and, if necessary, operations such as washing, filtration, drying, and grinding may be performed on the solid material mainly composed of zinc halide phthalocyanine pigment.

[0099] For cleaning, depending on the type of inorganic salt, water rinsing, hot water rinsing, cleaning with an organic solvent (e.g., an organic solvent with low surface tension such as methanol), or a combination thereof may be employed. Cleaning may be repeated in the range of 1 to 5 times. When water-soluble inorganic salts and water-soluble organic solvents are used, the organic solvent and inorganic salt can be easily removed by water rinsing. If necessary, acid cleaning or alkali cleaning may be performed.

[0100] As for drying after the washing and filtration described above, examples include batch or continuous drying in which the pigment is dehydrated and / or desolvated by heating to 80 to 120°C using a heating source installed in a dryer. Generally, examples of dryers include box dryers, band dryers, and spray dryers. In particular, spray drying using a spray dryer is preferred because it facilitates easy dispersion during paste production. When an organic solvent is used for washing, vacuum drying at 0 to 60°C is preferred.

[0101] Grinding after drying is not an operation to increase the specific surface area or reduce the average particle size of the primary particles, but is performed to break down the pigment into powder when the pigment has taken on a lamp shape, such as in the case of drying using a box dryer or a band dryer. Examples include grinding by a mortar and pestle, hammer mill, disc mill, pin mill, jet mill, etc.

[0102] In another embodiment, the second process includes preparing a mixture (hereinafter referred to as “mixture (B”)) containing a pigment and water and having a pH of 2 to 12, and heating the mixture (B) under a pressurized atmosphere (heating and pressurizing process).

[0103] According to the above heating and pressurizing process, the zinc halide phthalocyanine crude pigment can be refined while simultaneously controlling its orientation. Specifically, the heating and pressurizing process can be carried out using a heating and pressurizing device such as an autoclave. In an autoclave, a mixture (B) is placed in a container capable of heating and sealing installed in the autoclave, and by heating the mixture (B) while the container is sealed, the water contained in the mixture becomes steam, and the sealed space inside the container can be made into a pressurized atmosphere by said steam.

[0104] The amount of mixture (B) used is not specifically limited and may be appropriately changed depending on the size of the device used, etc.

[0105] The water content in the mixture (B) is preferably 300 parts by mass or more, more preferably 450 parts by mass or more, and even more preferably 600 parts by mass or more, with respect to 100 parts by mass of crude zinc phthalocyanine halide pigment, in order to make it easier to obtain a finer and more difficult-to-orient zinc phthalocyanine halide pigment by making it easier to get the pressure of the pressurized atmosphere within an appropriate range. The water content in the mixture (B) is preferably 6000 parts by mass or less, more preferably 4500 parts by mass or less, and even more preferably 3000 parts by mass or less, with respect to 100 parts by mass of crude zinc phthalocyanine halide pigment, in order to make it easier to get the pressure of the pressurized atmosphere within an appropriate range. The amount of water in the mixture (B) is preferably 10 to 90 volume% with respect to 100 volume% of the standard volume of the container, and more preferably 40 to 80 volume%.

[0106] The pH of the mixture is preferably 11.5 or lower, and more preferably 10 or lower, from the viewpoint that zinc halogenated phthalocyanine can be appropriately aggregated, making it easier to obtain a finer zinc halogenated phthalocyanine pigment that is also difficult to orient. The pH of the mixture is preferably 2.5 or higher, and more preferably 3 or higher, from the viewpoint that zinc halogenated phthalocyanine is not excessively aggregated. Furthermore, the above pH is the pH at 25°C. The pH of the mixture can be adjusted, for example, using a pH adjuster. As a pH adjuster, known and commonly used substances such as hydrochloric acid, sulfuric acid, phosphoric acid, potassium hydroxide, and sodium hydroxide may be used. Furthermore, the above pH is the pH at the start of heating, and in this embodiment, it is more preferable that the pH at the time of heating is within the above range.

[0107] The heating and pressurizing process includes, for example, a process of placing a mixture (B) in a sealed space, raising the atmosphere temperature of the sealed space to a predetermined temperature (final temperature reached), and a process of maintaining the atmosphere temperature at the said predetermined temperature (final temperature reached).

[0108] The heating start temperature (e.g., the ambient temperature inside the sealed space immediately after the mixture (B) is placed inside the sealed space) may be, for example, room temperature (20 to 30°C).

[0109] The predetermined temperature (final temperature reached) is preferably 80°C or higher and more preferably 100°C or higher from the perspective of facilitating the loosening of primary particle aggregation. The predetermined temperature (final temperature reached) is preferably 250°C or lower and more preferably 230°C or lower from the perspective of facilitating the prevention of primary particle coarsening. After reaching the predetermined temperature, it is preferable to maintain it at 80 to 250°C and more preferable to maintain it at 100 to 230°C.

[0110] The heating rate is preferably 10°C / min or less, more preferably 5°C / min or less, and even more preferably 3°C / min or less, from the perspective of making it easier to adjust particle size and to make it easier to break up aggregation of primary particles. The heating rate may be 0.1°C / min or more, 0.5°C / min or more, or 1°C / min or more.

[0111] The holding time at a predetermined temperature (final reached temperature) is preferably 30 minutes or more, and more preferably 60 minutes (1 hour) or more, from the perspective of making it easier to adjust the particle size. The holding time at a predetermined temperature (final reached temperature) is preferably 30 hours or less, and more preferably 10 hours or less, from the perspective of making it easier to prevent the coarsening of primary particles.

[0112] From the perspective of facilitating the loosening of primary particles, the pressure of the pressurized atmosphere is preferably 0.05 MPa or higher when a predetermined temperature is reached, more preferably 0.1 MPa or higher, and even more preferably 0.2 MPa or higher. From the perspective of preventing the coarsening of primary particles, the pressure of the pressurized atmosphere is preferably 2 MPa or lower when a predetermined temperature is reached, more preferably 1.8 MPa or lower, and even more preferably 1.7 MPa or lower.

[0113] Heating (e.g., raising and maintaining the temperature) in the heating and pressurizing process may be performed while stirring the mixture (B). Stirring of the mixture (B) may be performed, for example, by using an autoclave equipped with a stirring device such as a paddle or propeller within a sealed space as a heating and pressurizing device. As such a stirring device, for example, a concentric twin-screw stirrer manufactured by Asada Iron & Steel Co., Ltd. may be used. The stirring speed may be, for example, 30 to 200 rpm.

[0114] In the heating and pressurization process, an inert gas such as nitrogen or argon may be introduced into the sealed container.

[0115] After the heating and pressurizing process (for example, after the holding time ends), a solid material mainly composed of zinc halogenated phthalocyanine pigment can be obtained by cooling the treated material obtained by the heating and pressurizing treatment of mixture (B) by means of air cooling, etc. After cooling, if necessary, operations such as washing, filtration, drying, and grinding may be performed on the solid material mainly composed of zinc halogenated phthalocyanine pigment, in the same manner as after the grinding process described above.

[0116] Examples

[0117] The contents of the present invention will be explained in more detail below using examples and comparative examples, but the present invention is not limited to the following examples.

[0118] <Synthesis of Pigments>

[0119] (Synthesis of pigment A1)

[0120] In a 300ml flask, 91g of sulfuryl chloride (manufactured by Fujifilm Wako Pure Chemical Industry Co., Ltd.), 109g of aluminum chloride (manufactured by Kanto Chemical Co., Ltd.), 15g of sodium chloride (manufactured by Tokyo Kasei Industry Co., Ltd.), 30g of zinc phthalocyanine (manufactured by DIC Co., Ltd.), and 230g of bromine (manufactured by Fujifilm Wako Pure Chemical Industry Co., Ltd.) were added. The temperature was raised to 130℃ and maintained at 130℃ for 40 hours. After extracting the reaction mixture with water, it was filtered and washed to obtain aqueous crude pigment WA1. Subsequently, 10g of aqueous crude pigment WA1 was dried at 90℃ for 14 hours to obtain 4g of zinc phthalocyanine halide crude pigment (crude pigment A1). Additionally, washing was performed until the difference between the pH of the filtrate and the pH of the water used for washing was ±0.2.

[0121] Mass spectrometry was performed on crude pigment A1 using the JMS-S3000 manufactured by Nippon Electronics Co., Ltd., and it was confirmed to be zinc halide phthalocyanine with an average chlorine number of 1.8 and an average bromine number of 13.2. In addition, the delay time during mass spectrometry was 500ns, the laser intensity was 44%, and the resolving power value of the peak between m / z=1820 and 1860 was 31804.

[0122] (Synthesis of pigment A2)

[0123] 91 g of sulfuryl chloride (manufactured by Fujifilm Wako Pure Chemical Industry Co., Ltd.), 109 g of aluminum chloride (manufactured by Kanto Chemical Co., Ltd.), 19 g of sodium chloride (manufactured by Tokyo Kasei Kogyo Co., Ltd.), 28 g of zinc phthalocyanine (manufactured by DIC Co., Ltd.), and 230 g of bromine (manufactured by Fujifilm Wako Pure Chemical Industry Co., Ltd.) were added to a 300 ml flask. The temperature was raised to 140°C and maintained at 140°C for 40 hours. After extracting the reaction mixture with water, it was filtered and washed to obtain aqueous crude pigment WA2. Subsequently, 10 g of aqueous crude pigment WA2 was dried at 90°C for 14 hours to obtain 4 g of zinc phthalocyanine halide crude pigment (crude pigment A2). Additionally, washing was performed until the difference between the pH of the filtrate and the pH of the water used for washing was ±0.2. This pigment A2 is used as Reference Example 1.

[0124] Mass spectrometry was performed on the crude pigment A2 (Reference Example 1) using a JMS-S3000 manufactured by Nippon Electronics Co., Ltd., and it was confirmed to be zinc halide phthalocyanine with an average chlorine number of 2.0 and an average bromine number of 13.5. In addition, the delay time during mass spectrometry was 500ns, the laser intensity was 46%, and the resolving power value of the peaks from m / z = 1820 to 1860 was 30582.

[0125] <Example 1>

[0126] 0.3g of crude pigment A1, 3g of crushed sodium chloride, and 0.9g of 1,2,4-butanetriol were placed into an automatic Huber-Müller (Toyo Seiki Manufacturing Co.), and kneaded by applying a load of 150 lbs from the top of the glass plate and rotating the glass plate 25 times at 25°C. The mixture was scraped out with a spatula and put back in, and kneaded again by applying a load of 150 lbs from the top of the glass plate and rotating the glass plate 25 times at 25°C. Afterwards, the mixture was scraped out with a spatula and put back in, and kneaded again by applying a load of 150 lbs from the top of the glass plate and rotating the glass plate 50 times at 25°C. In addition, since the above kneading was performed at 100 rpm, the total grinding time was 1 minute.

[0127] Next, the mixture obtained above was placed in 200g of hot water and stirred for 1 hour. Afterward, green pigment G1 was obtained by filtering, washing, drying, and grinding.

[0128] <Example 2>

[0129] Green pigment G2 was obtained in the same manner as in Example 1, except that crude pigment A2 was used instead of crude pigment A1.

[0130] <Example 3>

[0131] 75g of aqueous crude pigment WA2 (crude pigment A2:water (mass ratio) = 6:4) was placed in a 1L autoclave along with 525g of water. Hydrochloric acid with a concentration of 5 mass% was used to adjust the hydrogen ion index of the material to be treated (a mixture of aqueous crude pigment WA2 and water) to pH 5.5, after which the autoclave was sealed. The pH was measured using a PH71 personal pH meter manufactured by Yokogawa Electric Co., Ltd. Subsequently, the temperature was raised to 200°C over 2 hours while stirring, and maintained at 200°C for 5 hours. The pressure inside the autoclave was 1.55 MPa when 200°C was reached. After cooling to room temperature, the resulting treated material was filtered, washed, dried, and ground to obtain green pigment G3.

[0132] <Reference Example 2>

[0133] 45g of crude pigment A2, 450g of ground sodium chloride, and 90g of water were placed in a double-arm kneader and kneaded at 60°C for 6 hours. The resulting mixture was then placed in 2kg of water at 80°C and stirred for 1 hour. Afterward, the mixture was filtered, washed in hot water, dried, and ground to obtain free pigment GP.

[0134] <Example 4>

[0135] 0.3g of free pigment GP, 3g of crushed sodium chloride, and 0.9g of 1,2,4-butanetriol were placed into an automatic Huber-Müller (Toyo Seiki Manufacturing Co.), and kneaded by applying a load of 150 lbs from the glass plate section and rotating the glass plate 25 times at 25°C. The mixture was scraped out with a spatula and put back in, and kneaded again by applying a load of 150 lbs from the glass plate section and rotating the glass plate 25 times at 25°C. Afterwards, the mixture was scraped out with a spatula and put back in, and kneaded again by applying a load of 150 lbs from the glass plate section and rotating the glass plate 50 times at 25°C. In addition, since the above kneading was performed at 100 rpm, the total grinding time was 1 minute.

[0136] Next, the mixture obtained above was placed in 200g of hot water and stirred for 1 hour. Afterward, green pigment G5 was obtained by filtering, washing, drying, and grinding.

[0137] <Example 5>

[0138] 12g of free pigment GP, 450g of crushed sodium chloride, and 61g of 1,2,4-butanetriol were placed in a double-arm kneader and kneaded at 20°C for 30 minutes. The mixture was then placed in 2 kg of water at 20°C and stirred for 1 hour. Afterward, green pigment G6 was obtained by filtering, washing, drying, and grinding.

[0139] <Comparative Example 1>

[0140] 40g of crude pigment A2, 400g of ground sodium chloride, and 63g of diethylene glycol were placed in a double-arm kneader and kneaded at 80°C for 8 hours. The mixture was then placed in 2 kg of water at 80°C and stirred for 1 hour. Afterward, green pigment G4 was obtained by filtering, washing, drying, and grinding.

[0141] <Evaluation>

[0142] (Measurement of average primary particle size)

[0143] Green pigments (G1~G6) were sonicated in cyclohexane and then photographed under a microscope. The average particle size of the primary particles (average primary particle size) was calculated from the average of 40 primary particles constituting the aggregates in the two-dimensional image. The results are shown in Table 1.

[0144] (Measurement of orientation parameters (A) and (C))

[0145] The orientation parameters (A) and (C) of crude pigment A2 and green pigments G1 to G6 were measured by the following method. Additionally, the case using crude pigment A2 is designated as Reference Example 1.

[0146] First, 0.992 g of crude pigment A2, free pigment GP, or green pigment (G1~G8) was mixed with 0.496 g of BYK-LPN6919 (Bic Chem, solution with 60 mass% solid content), 0.744 g of Unidic ZL-295 (manufactured by DIC Corporation, solution with 40 mass% solid content), and 4.368 g of propylene glycol monomethyl ether acetate, and 15.2 g of zircon beads of 0.3~0.4 mm were dispersed in a paint shaker manufactured by Toyo Seiki Co., Ltd. for 2 hours to obtain a dispersion (MG).

[0147] 3.000 g of the above dispersion (MG), 0.735 g of Unidic ZL-295 (manufactured by DIC Co., Ltd.), and 0.165 g of propylene glycol monomethyl ether acetate were added and mixed with a paint shaker to obtain an evaluation composition (CG) for measuring orientation.

[0148] An evaluation composition (CG) was spin-coated onto a glass substrate, dried at 90°C for 3 minutes, and then heated at 230°C for 1 hour. By doing so, a glass substrate for evaluating orientation was fabricated having a colored film on the glass substrate in which the mass ratio of crude pigment, free pigment, or green pigment (G1 to G6) and resin (solid content in Unidic ZL-295 and solid content in BYK-LPN6919) was 1:1.25. Additionally, by adjusting the spin rotation speed during spin-coating, the thickness of the colored film obtained by heating at 230°C for 1 hour was set to 4.0 μm. Corning (registered trademark) EAGLE XG (thickness 1.1 mm) was used as the glass substrate.

[0149] Using the BL03XU No. 1 Hatch, a beamline owned by the Industry-Academic Consortium dedicated to the development of frontier soft matter within the high-intensity synchrotron radiation experimental facility SPring-8, the measurement mode was set to Grazing Incidence Wide Angle X-ray Scattering (GI-WAXS), and GI-WAX measurements of a colored film on a glass substrate for orientation evaluation were performed under room temperature measurement conditions. The camera length was set to 102.5 mm, the X-ray wavelength to 0.1 nm, the X-ray incidence angle to 0.06°, and the exposure time to 5 seconds.

[0150] Orientation parameters (A) and (C) were obtained using the two-dimensional scattering images obtained by GI-WAXS measurement. The results are shown in Table 1, and the two-dimensional scattering images obtained in Reference Example 1, Comparative Example 1, and Example 3 are shown in FIG. 1 (a), (b), and (c), respectively. The azimuth profiles in the range of azimuth from 5° to 89° (a graph with the normalized average scattering intensity (normalized intensity) on the vertical axis and the azimuth on the horizontal axis) derived from these two-dimensional scattering images are shown in FIG. 2 (a), (b), and (c), and the azimuth profiles in the range of azimuth from 45° to 55° (a graph with the normalized average scattering intensity (normalized intensity) on the vertical axis and the azimuth on the horizontal axis) are shown in FIG. 3 (a), (b), and (c). Figure 2 is a graph regarding the orientation parameter (A), and Figure 3 is a graph regarding the orientation parameter (C).

[0151] As shown in FIG. 1, in Reference Example 1 ((a) in FIG. 1), the intensity in the 90° direction is large, and in Comparative Example 1 ((b) in FIG. 1), the intensity in the oblique direction is large, whereas in Example 3 ((c) in FIG. 1), the intensity is uniform and annular scattering can be obtained, and from a qualitative perspective, it can be seen that the orientation is relaxed in Example 3. Also, as shown in (c) in FIG. 2, in Example 3, the minimum / maximum value of the normalized average scattering intensity is 0.78 / 1.07, and the orientation parameter (A) satisfies 0.70 to 1.15. Also, as shown in (c) in FIG. 3, in Example 3, the slope of the linear approximation is 0.026, and the orientation parameter (C) satisfies -0.006 to 0.006.

[0152] (Evaluation of contrast and luminance)

[0153] 1.65 g of pigment yellow 138 (Chromofine Yellow 6206 EC manufactured by Dainichi Seika Co., Ltd.) was dispersed for 2 hours in a paint shaker manufactured by Toyo Seiki Co., Ltd. together with 3.85 g of DISPERBYK-161 (manufactured by Big Chem Co., Ltd.) and 11.00 g of propylene glycol monomethyl ether acetate using zircon beads of 0.3~0.4 mm. A dispersion was obtained.

[0154] A yellow color composition (TY1) was obtained by adding 4.0g of the above dispersion, 0.98g of Unidic ZL-295, and 0.22g of propylene glycol monomethyl ether acetate, and mixing with a paint shaker.

[0155] 2.48g of green pigments (G1~G6) were dispersed for 2 hours in a paint shaker manufactured by Toyo Seiki Co., Ltd. using zircon beads of 0.3~0.4mm with 1.24g of BYK-LPN6919 manufactured by Big Chem Co., Ltd., 1.86g of Unidic ZL-295 manufactured by DIC Co., Ltd., and 10.92g of propylene glycol monomethyl ether acetate to obtain a pigment dispersion (MG1) for color filters.

[0156] An evaluation composition (CG1) for forming a green pixel portion for a color filter was obtained by adding 4.0g of the above-mentioned pigment dispersion (MG1), 0.98g of Unidic ZL-295 manufactured by DIC Co., Ltd., and 0.22g of propylene glycol monomethyl ether acetate, and mixing with a paint shaker.

[0157] An evaluation composition (CG1) was spin-coated onto a glass substrate, dried at 90°C for 3 minutes, and then heated at 230°C for 1 hour. By doing so, a glass substrate for contrast evaluation was prepared having a colored film on the glass substrate. Additionally, by adjusting the spin rotation speed during spin-coating, the thickness of the colored film obtained by heating at 230°C for 1 hour was set to 1.8 μm. As the glass substrate, Corning (registered trademark) EAGLE XG (thickness 1.1 mm) was used.

[0158] In addition, a coating solution obtained by mixing the yellow coloration composition (TY1) and the evaluation composition (CG1) prepared above was spin-coated onto a glass substrate, dried at 90°C for 3 minutes, and then heated at 230°C for 1 hour. By doing so, a glass substrate for brightness evaluation having a colored film on the glass substrate was produced. In addition, by adjusting the mixing ratio of the yellow coloration composition (TY1) and the evaluation composition (CG1) and the spin rotation speed during spin-coating, a colored film was produced in which the chromaticity (x, y) of the colored film obtained by heating at 230°C for 1 hour was (0.275, 0.570) under a C light source. Corning (registered trademark) EAGLE XG (thickness 1.1 mm) was used as the glass substrate.

[0159] The contrast of the colored film on a glass substrate for contrast evaluation was measured using a contrast tester CT-1 manufactured by Tsubosaka Electric Co., Ltd., and the brightness of the colored film on a glass substrate for brightness evaluation was measured using a U-3900 manufactured by Hitachi High-Tech Science Co., Ltd. The results are shown in Table 1. In addition, the contrast and brightness values ​​shown in Table 1 are values ​​based on the contrast and brightness of Comparative Example 1.

[0160]

Claims

Claim 1 A zinc halogenated phthalocyanine pigment comprising 1.00 parts by mass of the pigment, 0.95 parts by mass of a benzyl methacrylate-methacrylic acid copolymer, and 0.30 parts by mass of a dimethylaminoethyl methacrylate copolymer, heated at 230°C for 1 hour to form an evaluation film with a thickness of 4 μm, and from a two-dimensional scattering image obtained by GI-WAXS measurement of the evaluation film, an average scattering intensity in the range where the scattering angle 2θ is 17° to 21° is obtained, and when a normalized average scattering intensity is obtained with the average scattering intensity at an azimuth angle of 45° as 1, the normalized average scattering intensity at an azimuth angle of 5° to 89° is 0.70 to 1.

15. Claim 2 A zinc halide phthalocyanine pigment according to claim 1, having an average primary particle size of 30 nm or less.

Citation Information

Patent Citations

  • Pigment dispersion composition, colored photosensitive composition, color filter, method for manufacturing a color filter, and liquid crystal display device.

    JP5689586B2

  • Pigment dispersion for color filter, coloring composition for color filter, color filter, and liquid crystal display device

    JP6489245B2

  • Pigment composition, coloring composition, and color filter

    JP7047679B2

  • Pigment composition for color filters, and color filter

    WO2018043548A1